Development of MATLAB-Based Physics Practical Media to Optimize Online Learning for Students on Sine Wave Material - Astalini, Astalini; Qizi, Karimova Charos Abduhalim; San, Min Thu; Yusifov, Sabuhi; Byamba-Ochir, Narandalai (Journal of Educational Technology and Learning Creativity, 2023)
Purpose of the study: This study aims to develop MATLAB-based learning media as an interactive online practicum tool to understand the concept of sine waves. Methodology: The research method uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research subjects are physics education students at Jambi University, data collection techniques using questionnaires. MATLAB-based media is designed with interactive simulation features that allow students to manipulate sine wave parameters, such as frequency, amplitude, and phase, in real-time. Main Findings: The test results showed that the majority of students responded positively to the use of this media, with 60% in the "Good" and "Very Good" categories. In addition, students' science process skills, such as data analysis and problem solving, also increased significantly, with an average score reaching 70.80. The results of the correlation test revealed a significant positive relationship (r = 0.542, p = 0.001) between students' responses to MATLAB development and science process skills. This interactive simulation provides a more intuitive learning experience than conventional methods, allowing students to understand abstract concepts visually and deeply. However, hardware and software limitations are challenges that need to be overcome for wider implementation. Novelty/Originality of this study: This research provides significant contributions in the development of simulation-based learning media for online education, especially in improving the understanding of physics concepts and science process skills. In the future, web-based development or mobile applications are proposed to improve accessibility and efficiency of learning.